The relationship between the roots and furcation of the maxillary first molar to the maxillary sinus: A cone-beam computed tomography study - Girish Katti; Syed Shahbaz; Chandrika Katti; Mohd Sabyasachi Rahman (Wolters Kluwer Medknow Publications, 2018)
Introduction: Pneumatization of maxillary sinus leads to posterior root displacement into the sinus cavity associated with potential complications following extraction of these teeth, or planning an implant in case of missing ones. Thus the relation of the maxillary sinus to the maxillary posterior teeth is of utmost importance. Hence the study was taken up to evaluate the relation of maxillary first molar to the maxillary sinus. Objectives: Assessing the relationships between the roots and furcation of the maxillary first molar to the floor of the maxillary sinus. Materials and Methods: A retrospective study where 50 CBCT scans of maxillary first molars of 36 patients were taken and the vertical relationship of the roots and furcation with the floor of the sinus were analyzed and classified. Results: Totally 14 (28%) mesio buccal roots, 8 (16%) disto buccal roots and 5 (10%) palatal roots were in Class 3, which is perforating into the sinus and total of 18 scans had furcations whose distance from the sinus floor was less than 5mm with Mean ± SD as 3.64 ± 1.14 and rest had more than 5mm with Mean ± SD as 6.19 ± 2.63 Conclusion: Our study concluded that though most roots were not in touch with the maxillary sinus, a notable amount were either in touch or penetrating into it. Thus any pathology assessment or treatment plan in the first molar region must be dealt with proper three dimensional images to understand the approximation of the sinus and plan out procedure best suited for the patient.